Aspectos analítico-interpretativos e a estética armorial no concertino em lá maior para violino e orquestra de cordas, de Clóvis Pereira - Marinho, Marina Tavares Zenaide (2010)
This research intends to study the historical, aesthetic, and interpretative aspects of Clóvis Pereira s Concertino in A Major for Violin and String Orchestra (1996-2001) a unique concertante work written for the violin in the armorial style. Thus, the main goal of this dissertation is to offer interpretative ideas based on the analysis of the most important aspects of this aesthetics. For this intent, we have done personal interviews with the composer, performers and scholars. We have also done extensive research in the composer personal files and archives, as well as at the Joaquim Nabuco s Foundation and the Federal University of Pernambuco libraries. The analysis of the piece was focused mainly on the observation of the compositional process, besides the idiomatic use of the instrument and its relationships with popular and folkloric references as agents of the musical style. The hypotheses were evaluated and confirmed empirically, demonstrating the significance of theoretical study, and its relation to interpretative issues, in the search for a better performance.